STUDY ON THE OVEREXPRESSION OF IGF1 AND CRIP 1 IN CHILDREN OSTEOSARCOMAS - A.Ivan; Luminita Ivan; N.Forna; Ludmila Lozneanu; P.D. Sirbu (Romanian Society of Oral Rehabilitation, 2024)
Considering that osteosarcoma in children is the most common bone tumor and is characterized by an aggressive evolution, the problem arises of a more personalized treatment to increase the survival rate. In researching new and reliable biomarkers we identified IGF1 (insulin-like polypeptide hormone) and CRIP-1 (Cysteine-Rich Intestinal Protein 1). Their overexpression has been documented to have a significant prognostic impact on different. Therefore, we aimed to investigate the overexpression of IGF1 and CRIP-1 in pediatric osteosarcoma and assess their potential as a prognostic biomarker. Marterial and methods: We analyzed 65 samples from patients diagnosed with osteosarcoma at "Sf. Maria" Emergency Clinical Hospital for Children from Iasi, between 2017 and 2021 The staining kits were used is Mouse and Rabbit Specific HRP/DAB (ABC) Detection IHC Kit from Abcam and monoclonal antibody antiIGF1 and polyclonal antibody CRIP 1.Results:Both Igf 1 and CRIP-1 were overexpressed in over 90% of the cases. The lower the degree of differentiation, the less CRIP-1 is overexpressed and the more frequently it is found in the nucleus.We don t identified the ov no exclusive nuclear expression, (associated with a favorable prognosis) for IGF1.Conclusion:Could this mean that CRIP-1 overexpression is associated with a better prognosis? Could this mean that IGF1 overexpression is associated with a poor prognosis? The study highlights the clinical implications of Igf1 and CRIP-1 in osteosarcoma, emphasizing their importance for prognosis, and personalized treatment strategies.